Development of interactive e-books to increase learning independence in statistics - Nugroho, Aryo Andri; Dwijayanti, Ida; Setyawati, Rina Dwi (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2023)
The purpose of this research in general is to develop statistics teaching materials in the form of e-modules by applying Microsoft excel in it. The implementation of the use of statistics teaching materials in lectures is still not optimal. This research offers solutions for the use of teaching materials in the form of e-books that are easy to understand in statistics courses to increase student learning independence. This activity emphasizes more on measuring the achievement of e-modules clearly in their application and implementation in learning. This research uses  the Borg & Gall research and development pattern method  with 10 steps. The results showed that the assessment of media aspects in the form of E-books by media expert validators covering general aspects, aspects of material substance, aspects of language feasibility, and aspects of graphic feasibility obtained a percentage of 88.7% were in very good qualifications. Assessment on the material aspect found that the percentage of product feasibility of 95% was in very good qualification. From the assessment of media experts and material experts, the products in this study are feasible or valid to use. In the readability test by students, the average percentage is 80.6%, meaning that it is very easy to understand.